Pengaruh Model Pembelajaran Kooperatif Tipe Think-Pairs-Share Dalam Pembelajaran Matematika Terhadap Kemampuan Pemahaman Konsep Matematis dan Pengembangan Karakter Siswa SMA Kota Sungai Penuh - Maila Sari; Mhmd Habibi; Rahmi Putri (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Kerinci, 2018)
Mathematics teachers are required not only to transfer knowledge to learners but also to shape and develop the character of students in the learning process of mathematics. To be able to grow and develop the character of students required a model of learning that can bring the character formation indicators in the learning process. The learning model that can generate character development indicators is a Think-Pairs-Share (TPS) model of learning. This study aims to determine 1) the ability to understand students' concepts using the TPS learning model and the ability to understand students' concepts that do not use the TPS learning model, 2) the honest character, responsibility, and discipline of students using the TPS learning model and the honest character, and discipline students who do not use the TPS learning model. The result of data analysis shows that: 1) the ability of students' concepts understanding using the TPS learning model is better than the students' concepts comprehension skills that do not use the TPS learning model, 2) the honest character, responsibility, and discipline of students using the TPS learning model more both compared to the honest characters, responsibility, and discipline of students who do not use the TPS learning model.